WORKSHOP PEMROGRAMAN SCRATCH UNTUK YATIM & PIATU YAYASAN GRIYA SODAQO INDONESIA - Al Anshary, Faishal Mufied; Fauzi, Rahmat; Hamami, Faqih (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2023)
Griya Sodaqo Indonesia Foundation is a charity organization that focuses on orphans and children especially in the city of Bandung. However, these children often do not have the opportunity to learn programming and technology, which are very important skills in today's digital age. As an effort to provide opportunities to learn programming for children at the Griya Sodaqo Foundation. Information Systems Lecturer at the Faculty of Industrial Engineering, Telkom University, organizes a Visual Scratch Programming Workshop in an easy and easy-to-understand way. With this workshop, children learn about programming concepts in a creative and interactive way. Through this workshop, orphans at Griya Sodaqo get relevant skill opportunities and become confident in facing future technological challenges. The results of this workshop activity 96% of participants were very enthusiastic about this agenda by providing feedback, they strongly agreed with the implementation of basic programming training with Scratch.